Upper and Lower Bounds for the Kirchhoff Index of the n-Dimensional Hypercube Network - Jia-Bao Liu; Jing Zhao; Zhi-Yu Shi; Jinde Cao; Fuad E. Alsaadi (Complexity)
The hypercube Qn is one of the most admirable and efficient interconnection network due to its excellent performance for some practical applications. The Kirchhoff index KfG is equal to the sum of resistance distances between any pairs of vertices in networks. In this paper, we deduce some bounds with respect to Kirchhoff index of hypercube network Qn.